Immature CD8 Single-Positive Thymocytes Are a Molecularly Distinct Subpopulation, Selectively Dependent on BRD4 for Their Differentiation - Anne Gegonne; Qing-Rong Chen; Anup Dey; Ruth Etzensperger; Xuguang Tai; Alfred Singer; Daoud Meerzaman; Keiko Ozato; Dinah S. Singer (Cell Reports, 2018)
Summary: T cell differentiation in the thymus proceeds in an ordered sequence of developmental events characterized by variable expression of CD4 and CD8 coreceptors. Here, we report that immature single-positive (ISP) thymocytes are molecularly distinct from all other T cell populations in the thymus in their expression of a gene profile that is dependent on the transcription factor BRD4. Conditional deletion of BRD4 at various stages of thymic differentiation reveals that BRD4 selectively regulates the further differentiation of ISPs by targeting cell cycle and metabolic pathways, but it does not affect the extensive proliferation that results in the generation of ISPs. These studies lead to the conclusion that the ISP subpopulation is not a hybrid transitional state but a molecularly distinct subpopulation that is selectively dependent on BRD4. : Thymocytes differentiate from immature DN to ISP, DP, and single-positive thymocytes. Gegonne et al. report the finding that BRD4 is required at the transition from immature ISP to DP thymocytes but not for the differentiation of DN thymocytes or the maturation of conventional single-positive thymocytes from the DP stage. Keywords: differentiation, immature single-positive thymocytes, ISP, BRD4, gene expression, cell cycle, metabolic pathways, c-Myc